Language proficiency in native and non-native speakers : theory and research - Hulstijn, Jan Hendrik (Language learning and language teaching, 2015)
This book, written for both seasoned and novice researchers, presents a theory of what is called Basic and Higher Language Cognition (BLC and HLC), a theory aimed at making some fundamental issues concerning first and second language learning and bilingualism (more) empirical. The first part of the book provides background for and explication of the theory as well as an agenda for future research, while the second part reports on selected studies of language proficiency in native speakers, as well as non-native speakers, and studies of the relationship between literacy in a first and second la.